Interactions between starch source and gelatinisation degree on performance and small intestinal digestion in broiler chickens. Issue 3 (4th May 2021) - Itani, K.; Hansen, J. Ø.; Kierończyk, B.; Benzertiha, A.; Kurk, P. P.; Ånestad, R. M.; Sundby, F.; Mydland, L. T.; Øverland, M.; Svihus, B.
ABSTRACT: 1. A 2 × 2 factorial arrangement was used to test the hypothesis that, in pelleted diets, legume starch is digested less rapidly and to a lesser extent than cereal starch, and that increased gelatinisation through extrusion would eliminate the differences between the starch sources. In addition, the trial examined whether a lower ratio of starch to nitrogen disappearance rate (SNDR) could improve feed conversion ratio (FCR). 2. At 17 d of age, male broilers were randomly distributed among four dietary treatments, consisting of either wheat or faba bean starch-rich fraction (FBS) as the sole starch source and pelleting or extrusion as processing methods. Each treatment had 10 replicate pens containing five birds each. 3. Extrusion resulted in a more extensive starch gelatinisation compared to pelleting, as expected. 4. No difference in weight gain at 29 d of age was observed between birds fed starch sources. However, birds fed wheat tended (P = 0.080) to have better FCR than those fed FBS, while the effect of processing methods was insignificant. Thus, there was no interaction between starch source and processing method on FCR. 5. In pelleted diets, FBS had lower and slower starch digestibility compared to wheat in all intestinal segments (P < 0.05). The interaction between starch source and processing method in all intestinal segments (P < 0.001) demonstrated that FBS responded more to gelatinisation through extrusion than did wheat. Thus, differences in starch digestibility between the wheat and FBS were eliminated with extrusion. 6. Feeding extruded diets significantly increased the upper jejunal expression of GLUT1, GLUT2 and SGLT1 compared to pelleted diets, which suggested that glucose absorption was less likely to be a limiting factor for starch utilisation. 7. Pelleting resulted in a lower ratio (P < 0.001) of SNDR compared to extrusion (on average 1.4-fold) but did not improve FCR.